PARKING SPACE AS A NEW OBJECT OF REAL ESTATE: PROBLEMS OF THEORY AND PRACTICE - M. A. Bychko; M. P. Melnikova (Гуманитарные и юридические исследования)
The Russian legislator has inally determined the legal nature of a parking lot by means of simplification of its civil law circulation. Since 1 January 2017 the Civil Code of the Russian Federation deines it as an independent object of real estate. The changes affected the norms of the Town Planning Code, the cadastre law, state registration of real estate law. The acts of the Russian Federation Ministry of Economic Development, which codify, specify and clarify the concept and the legal regime of a parking lot, have come into force.